Correlation of CBR with Index Properties of Soil - Mahajan, Vikaran (My University, 2014)
California bearing ratio is most used indirect method to assess the stiffness modulus and shear strength of subgrade in the design of flexible pavement. The type of soil not only affects the CBR value, but the CBR value also varies with different properties possessed by the soil. CBR value of soil depends on many factors like maximum dry density (MDD), optimum moisture content (OMC), liquid limit (LL), unconfined compressive strength, percent fines etc. Determination of CBR is a bit lengthy and time consuming process. In this study, soil samples were taken from 11 different locations within 50 km radius of Patiala city and various tests were performed on these sample. An attempt has been made to correlate soaked as well as unsoaked CBR value with percent fines, LL, MDD and OMC. ANN model is also developed to established best linear fit between the experimental values and the literature value. The correlation is established in the form of an equation of CBR as a function of different soil properties by the method of regression analysis. It has been observed that the predicted values are in the domain of experimental values and the results indicated a strong correlation with value of r2=0.901 for unsoaked CBR and r2= 0.897 for soaked CBR.
ME, CED
Keywords: Index properties of Soil; CBR; ANN; MRA; CED